'Get alongside us', women's experiences of being overweight and pregnant in Sydney, Australia. Issue 3 (13th December 2011) - Mills, Annie; Schmied, Virginia A.; Dahlen, Hannah G.
Abstract Studies of women's experiences of being overweight and pregnant are limited in the literature. Given the increasing rates of obesity in pregnant women, and the impact of being overweight on the health of the mother and the child, this qualitative descriptive study aimed to explore the perceptions and experiences of overweight pregnant women attending two maternity units in Sydney, Australia. Fourteen women aged between 25 and 42 years with a body mass index greater than 30 kg/m2 participated in a face‐to‐face interview in their third trimester of pregnancy or in the early post‐natal period. All interviews were recorded and transcribed. Field notes were also recorded following each interview. Data were analysed using thematic analysis. Four themes were identified in the data: 'being overweight and pregnant', 'being on a continuum of change', 'get alongside us' and finally 'wanting the same treatment as everyone else'. Most women recognised their weight as an issue both for their own health and well‐being and for its impact on the baby. Women believed health professionals should address the issue of obesity with them but do so in a supportive and positive way that recognised their individual needs and expectations. Health professionals need to consider new approaches or models of care for overweight women that give them support and enable individual needs and expectations to be met. Culturally specific programs may also need to be developed.